Novel Pyridine‐Based Hydroxamates and 2′‐Aminoanilides as Histone Deacetylase Inhibitors: Biochemical Profile and Anticancer Activity. (16th December 2020) - Zwergel, Clemens; Di Bello, Elisabetta; Fioravanti, Rossella; Conte, Mariarosaria; Nebbioso, Angela; Mazzone, Roberta; Brosch, Gerald; Mercurio, Ciro; Varasi, Mario; Altucci, Lucia; Valente, Sergio; Mai, Antonello
Abstract: Starting from the N ‐hydroxy‐3‐(4‐(2‐phenylbutanoyl)amino)phenyl)acrylamide (5 b ) previously described by us as a HDAC inhibitor, we prepared four aza‐analogues, 6 –8, 9 b, as regioisomers containing the pyridine nucleus. Preliminary screening against mHDAC1 highlighted the N ‐hydroxy‐5‐(2‐(2‐phenylbutanoyl)amino)pyridyl)acrylamide (9 b ) as the most potent inhibitor. Thus, we further developed both pyridylacrylic‐ and nicotinic‐based hydroxamates (9 a, 9 c –f, and 11 a –f ) and 2′‐aminoanilides (10 a –f and 12 a –f ), related to 9 b, to be tested against HDACs. Among them, the nicotinic hydroxamate 11 d displayed sub‐nanomolar potency (IC50 : 0.5 nM) and selectivity up to 34 000 times that of HDAC4 and from 100 to 1300 times that of all the other tested HDAC isoforms. The 2′‐aminoanilides were class I‐selective HDAC inhibitors, generally more potent against HDAC3, with the nicotinic anilide 12 d being the most effective (IC50 HDAC3 =0.113 μM). When tested in U937 leukemia cells, the hydroxamates 9 e, 11 c, and 11 d blocked over 80 % of cells in G2/M phase, whereas the anilides did not alter cell‐cycle progress. In the same cell line, the hydroxamate 11 c and the anilide 10 b induced about 30 % apoptosis, and the anilide 12 c displayed about 40 % cytodifferentiation. Finally, the most potent compounds in leukemia cells 9 b, 11 c, 10 b, 10 e, and 12 c were also tested in K562, HCT116, and A549 cancer cells, displaying antiproliferative IC50 values at single‐digit to sub‐micromolar level. Abstract : Choose your weapon : The HDAC inhibitory behavior of pyridine‐based hydroxamates and 2′‐aminoanilides is described. The nicotinic hydroxamates, especially 11 d, proved very potent against HDAC6 with a selectivity index ranging from 100 to 30 000 times that of other HDACs. Hydroxamate 11 c displayed the highest apoptosis induction, whereas anilide 12 c was the best at inducing cytodifferentiation in leukemia U937 cells.